Akysis pulvinatus, a new species of catfish (Siluriformes: Akysidae) from southern Thailand - Ng, Heok Hee (Zootaxa, 2007)
Akysis pulvinatus, new species, is described from southern Thailand. It can be distinguished from congeners in having a combination of: length of adipose-fin base 23.0–25.2% SL, body depth at anus 13.2–16.0% SL, caudal peduncle depth 9.4–10.3% SL, head length 27.6–29.8% SL, head width 21.9–25.1% SL, length of nasal barbel 13.9–57.5% HL, length of maxillary barbel 78.5–105.0% HL, smooth posterior edge of pectoral spine, gently forked caudal fin with lower lobe longer than upper, yellow snout, and rounded pale colored patches on body. A possible case of Müllerian mimicry with the syntopic Pseudobagarius leucorhynchus is mentioned and briefly discussed.